ANALISIS KEPUASAN WISATAWAN NUSANTARA YANG MENGGUNAKAN JASA CUSTOMER SERVICES DI LOMBOK INTERNATIONAL AIRPORT - Amelia Helena Ratu, Heidy; Sudiarta, I Nyoman; Agus Wikanatha Sagita, Putu (Jurnal IPTA (Industri Perjalanan Wisata), 2021)
This research aims to determine the satisfaction level of domestic tourists toward the service of customer services at Lombok International Airport. In this study, collecting data by observation, questionnaires, literature study and documentation. Determination of the sample using purposive sampling technique by distributing questionnaires to 100 respondents. The data analysis technique is conducted with the customer satisfaction index and importance performance analysis (IPA). The results showed that the average importance level of the indicator was 4.38 which was categorized as very important. Meanwhile, the performance level of customer services obtained an average score of 3.02 which is categorized as quite good. The calculation of the overall gap value obtained an average value of -1.36, which means that there is a gap between expectations and the performance of the officers. The calculation result of the customer satisfaction index is 60.36%, which means that tourists are quite satisfied with the service quality of customer services.  The most important and high prioritized indicators are the politeness of officers in communicating, providing service according to SOP, ability to handle complaints, knowledge and insight of officers, as well as the ability of handling problems promptly. In order to improve the satisfaction level of the tourist.